A Quantitative Assessment on Perceived Physiological Comfort of Clothing during Lactation - Jayanthi Kandiah; Diana Saiki; Fatima Alshhree (Journal of Social Behavior and Community Health)
Background: Physiological comfort refers to sensorial comfort including temperature, fit and fabric weight. Because pregnant and lactating women undergo various physiological changes, it is important to identify optimal comfort features regarding clothing. This will promote and increase breastfeeding duration. The purpose of this research is to compare physiological comfort of two types of clothing. They include designed clothing (DC) ,such as side flaps to access breasts and a strap which gets unhooked ), and conventional clothing(CC), like center front button closure, center front zipper, knitted V-neck shirt, and a t-shirt. Methods: This was a quantitative research study conducted to examine perceived physiological comfort of clothing during lactation (IRB# 1-1056432-1). Data were collected from 217 lactating women who were on lactated related social media sites (e.g., BabyCenter blog). A validated and reliable survey was developed by interviewers. It was a series of questions including demographic ones and assessed seven physiological features.  Data were analyzed using descriptive statistics, frequencies (number and percent), and, a sample t-test. Results:  After comparing DC with CC, authors found that DC provided greater physiological comfort.  Statistically significant differences (p≤ .05) were found between garment coverage in reference to temperature (i.e. warmth) and satisfaction with the length of the garment. Conclusion: The results have practical implications for a variety of professions including apparel designers and lactation health care providers. Currently, there is little to no research which investigated physiological comfort of outerwear clothing for lactating mothers.